Neuropsychological and Language Deficits in 22q11.2 Deletion Syndrome - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Bambino Genu Children's Hospital, Rome, and multiple additional centers in Italy conducted a retrospective and prospective study of clinical manifestations at diagnosis and during follow-up of 228 patients with 22q11.2 deletion syndrome.